Chronic exposure to cannabinoids during adolescence causes long‐lasting behavioral deficits in adult mice. (31st August 2016) - Tomas‐Roig, J; Benito, E; Agis‐Balboa, RC; Piscitelli, F; Hoyer‐Fender, S; Di Marzo, V; Havemann‐Reinecke, U
Abstract: Regular use of marijuana during adolescence enhances the risk of long‐lasting neurobiological changes in adulthood. The present study was aimed at assessing the effect of long‐term administration of the synthetic cannabinoid WIN55212.2 during adolescence in young adult mice. Adolescent mice aged 5 weeks were subjected daily to the pharmacological action of WIN55212.2 for 3 weeks and were then left undisturbed in their home cage for a 5‐week period and finally evaluated by behavioral testing. Mice that received the drug during adolescence showed memory impairment in the Morris water maze, as well as a dose‐dependent memory impairment in fear conditioning. In addition, the administration of 3 mg/kg WIN55212.2 in adolescence increased adult hippocampal AEA levels and promoted DNA hypermethylation at the intragenic region of the intracellular signaling modulator Rgs7, which was accompanied by a lower rate of mRNA transcription of this gene, suggesting a potential causal relation. Although the concrete mechanisms underlying the behavioral observations remain to be elucidated, we demonstrate that long‐term administration of 3 mg/kg of WIN during adolescence leads to increased endocannabinoid levels and altered Rgs7 expression in adulthood and establish a potential link to epigenetic changes. Abstract : Adolescent mice were subjected daily to WIN55212.2, then left undisturbed, and finally evaluated by behavioral testing at adulthood. Mice that received the drug during adolescence showed memory impairment, higher endocannabinoid levels and altered Rgs7 expression in adulthood, establishing a potential link to epigenetic changes.